Fuconxanthin as Antiobesity - Agustina D. R. Nurcahyanti; Kris H Timotius (Jurnal Teknologi dan Industri Pangan, 2007)
Fucoxanthin is a member of pigment of xantophlly-carotenoid and a major pigment found in some brown algae. Studies about this pigment revealed the advantages of fucoxanthin as active biological component. One of them is a antiobesity activity. The mechanism of this activity was discribed as increasing UCP1 protein expression in white adipose tissue. increasing UCP1 protein expression associated with thermogenesis process which lead the releasing energy carries fatty acids to out of membrane and converted as converted as het. In addition, fucoxanthin can lead liver to produse DHA although the mechanism was not understood clearly. Antiobesity activity of fucoxanthin direct to create the new nTURl aupplement which low in side effects. Key word : antiobesity, fucoxanthin, Uncoupling Protein (UCP)